A Compact Low-Cost Camera Module with Modified Magnetic Restoring Force. (12th January 2017) - Liu, C. S.; Tsai, B. J.; Chang, Y. H.
Abstract : In recent years, compact camera modules (CCMs) have been widely used in consumer electrical and electronic products. CCMs with low cost specially are necessary for portable devices. Therefore, the present group recently developed a miniaturized open-loop controlled camera module with low cost for cellphone applications, in which the Lorentz force is balanced by a magnetic restoring force. To enhance the performance of the camera module, this article reports a pattern structure to modify the linearity of the magnetic restoring force. We fabricated a CCM prototype with the dimensions of 8.5 mm × 8.5 mm × 5 mm and demonstrated the usefulness of the pattern structure with the CCM prototype. Its potential applications are foreseeable in portable devices, such as cellphones, web cameras, personal digital assistants and other commercial electronics.